Multifactorial Benefits of Chronic Vagus Nerve Stimulation on Autonomic Function and Cardiac Electrical Stability in Heart Failure Patients With Reduced Ejection Fraction - Verrier, Richard L.; Libbus, Imad; Nearing, Bruce D.; KenKnight, Bruce H. (Frontiers in Physiology, 2022)
Heart failure with reduced left ventricular ejection fraction is a progressive disease that claims >352,000 lives annually in the United States alone. Despite the development of an extensive array of pharmacologic and device therapies, prognosis remains poor. Disruption in autonomic balance in the form of heightened sympathetic nerve activity and reduced vagal tone have been established as major causes of heart failure progression. Interest in chronic neuromodulation mediated by vagus nerve stimulation (VNS) has intensified in recent years. This review focuses on four main goals: 1. To review the preclinical evidence that supports the concept of a cardioprotective effect of VNS on autonomic function and cardiac electrical stability along with the underlying putative mechanisms. 2. To present the initial clinical experience with chronic VNS in patients with heart failure and highlight the controversial aspects of the findings. 3. To discuss the latest findings of the pleiotropic effects of VNS on autonomic tone, baroreceptor sensitivity, and cardiac electrical stability and the state-of-the-art methods employed to monitor these relationships. 4. To discuss the implications of the current findings and the gaps in knowledge that require attention in future investigations.